(untitled) (Edad Media. Revista de Historia, 2024)
The last war against Granada (1482-1492) marked a turning point in the revenue obtained from the extraordinary income of the Crusade. The analysis of the accounts rendered by the different treasurers and commissioners in charge of its management in Andalusia allows us not only to get a closer look at the structure of this resource, but also to approach the profile of the collectors. Therefore, the aims of this article are to study the professional background of the agents involved, as well as the different ways of accessing this position, in order to help us understand the interests behind the management of a resource which at this time was on its way to become one of the main financial instruments of the Hispanic monarchy.